BEHAVIOURAL FINANCE IN AGRIBUSINESS – THE BIRTH OF A CONCEPT - Pawlonka, Tomasz (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
Up until now, a model approach has constituted the core of mainstream economics with regard to the decision maker and decision-making conditions. The financial (and economic) crises appearing with increased frequency and numerous market anomalies, although considered predictable by economists and being only a residual component of econometric models, are related to the growing financialization of the economy and an existing asymmetry of information in the absence of full decision-maker rationality. The importance of the psychological characteristics of individuals, their knowledge, the level of trust and priorities, recognized more and more commonly in economic practice, make it necessary to conduct research to identify ‘difficult quantifiable’ characteristics of decision-makers, including their purely economic considerations. (as a supplement to previous economic considerations, including the inclusion of new variables to econometric models that have been in operation for years). The aim of the study was to systematize the evolution of the homo oeconomicus concept along with an indication of further possible directions in its development. A survey of behavioural finance in relation to agribusiness has also been reviewed, which is a perfect example of the evolution of mainstream economics.